The Case of the Dissenters in a Letter Addressed to the Lord Chancellor - Anonymous, Anonymous (Analecta Gorgiana, 2010)
The article is a letter concerning the treatment of Dissenters in England. The writer objects to the nationalized Episcopacy for various injustices upon Dissenters. He asks for separation of church and state